Sekolah Asik Tanpa Plastik: Edutainment Dampak dan Pencegahan Mikroplastik di Lingkungan Sekolah - Nurika, Globila; Pujiati, Rahayu Sri; Khoiron, Khoiron; Irbah, Nafi’atul; Azizah, Qisma Farah; Putri, Sang Ayu Putu Ardya Pramesthi Reggina (UPT Penerbitan Universitas Jember, 2023)
Background: Waste generation in Indonesia reaches 34.584.584,16 tons/year with 17.1% being plastic waste. Environmental management education for elementary school children is the right first step in fostering a sense of love for the environment. These activities which are carried out in a sustainable manner will reduce the phenomenon of plastic waste emergencies in the environment which will lead to an increase in the amount of microplastics in the environment. Method: This edutainment activity packs educational activities in an interesting way by carrying out the concept of learning while playing with a word guessing game. Media posters were also used in this activity. The target of the activity is grade 5 and 6 students of SDN 1 Subo. Evaluation of the success of this activity is by carrying out pre-test and post-test activities. Results: The edutainment activities were enthusiastically attended by students. The results of the evaluation of achievement indicators of success also show that more than 80% of student scores have increased after edutainment activities. In addition, the results of statistical tests using the paired sample t-test also show that there is an effect of edutainment interventions in increasing the knowledge of SDN 1 Subo students on the impacts and dangers of microplastics to nature and the human body, as well as ways to reduce microplastics in the environment. Conclusion: Overall the edutainment activities regarding knowledge about the impacts and dangers of microplastics for nature and the human body, as well as ways to reduce microplastics in the environment ran smoothly and succeeded in achieving the target indicator of more than 80% pre-test and post-test students had increased.Keywords: environmental education, the dangers of microplastics, plastic waste.